Screening of Drugs Inhibiting In vitro Oligomerization of Cu/Zn-Superoxide Dismutase with a Mutation Causing Amyotrophic Lateral Sclerosis - Anzai, Itsuki; Toichi, Keisuke; Tokuda, Eiichi; Mukaiyama, Atsushi; Akiyama, Shuji; Furukawa, Yoshiaki (Frontiers in Molecular Biosciences, 2016)
Dominant mutations in Cu/Zn-superoxide dismutase (SOD1) gene have been shown to cause a familial form of amyotrophic lateral sclerosis (SOD1-ALS). A major pathological hallmark of this disease is abnormal accumulation of mutant SOD1 oligomers in the affected spinal motor neurons. While no effective therapeutics for SOD1-ALS is currently available, SOD1 oligomerization will be a good target for developing cures of this disease. Recently, we have reproduced the formation of SOD1 oligomers abnormally cross-linked via disulfide bonds in a test tube. Using our in vitro model of SOD1 oligomerization, therefore, we screened 640 FDA-approved drugs for inhibiting the oligomerization of SOD1 proteins, and three effective classes of chemical compounds were identified. Those hit compounds will provide valuable information on the chemical structures for developing a novel drug candidate suppressing the abnormal oligomerization of mutant SOD1 and possibly curing the disease.